Perancangan Sistem Informasi E-Tiket Wisata Air Terjun Tri Sakti Menggunakan Metode Agile - Rita Wati; Sri Handayani; Surya Ade Saputera (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Tri Sakti Waterfall Tourism Object still uses a manual system for ticket sales and visitor data recording, which causes several problems such as ticket purchase queues, data recording errors, and delays in report preparation. This study aims to design an E-Ticket Information System to support ticket management, visitor data management, ticket validation, and report generation more effectively. The method used in this study is Agile Software Development with the Scrum approach. Data were collected through observation, interviews, documentation, and literature review. The system design process includes the development of Context Diagrams, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), database design, and user interface design. The result of this study is a web-based E-Ticket Information System design involving administrators, ticket officers, and visitors. The system provides features such as registration, login, online ticket booking, payment processing, ticket validation, data management, and report generation. The proposed system is expected to improve ticket service efficiency by making processes faster, more accurate, and well-organized, while reducing queues, minimizing data recording errors, and supporting the digitalization of tourism management at Tri Sakti Waterfall Tourism Object.